MODEL BLUE ECONOMY DI KAWASAN ASIA PASIFIK (STUDI KASUS: PENERAPAN MODEL BLUE ECONOMY PADA INDUSTRI PERIKANAN INDONESIA) - Wulandari Cahayasari; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research explains about blue economy models in Asia Pacific region, especially the implementation of the blue economy models in Indonesia fisheries industry. Asia Pacific Economic Cooperation (APEC) is a forum of economic cooperation countries of Asia Pacifik which aims to improve the welfare and economic growth has a vision of marine and fisheries which competitive and sustainable for community welfare. To realize the vision of marine and fisheries development implemented by blue economy models.This research used primary data which derived from interviews, official document government and APEC, and used secondary data which derived from review of the literature and also used qualitative methods with descriptive analysis approach, namely how to describe and analyze the various situation of the issues under study and to support the facts that occurred.Based on the results of the research showed that the function of APEC seen its role to facilitate the economic growth of member countries with the agreement achievement the blue economy of commitment to form partnerships more integrated, sustained, inclusive and mutually beneficial. In addition, Indonesia has the potential of fishery commodities, Indonesia utilize the opportunity to contribute significantly in the implementation stage of blue economy models in sector of the fisheries industry.Keywords: Blue Economy, Asia Pacific Economic Cooperation (APEC), Sustainable Development, Fisheries Industry